Кәмил инсан болып жетилисиўде дене тәрбия ҳәм спорттың әҳмийети - Еримбетов, Б.Қ (SCIENCE and SOCIETY, 2022)
The article deals with the role of the national struggle in the formation of national pride among the youth. The significance of the na- tional struggle in the spiritual preparation of the youth is scientifically substantiated. The struggle is also considered as factors that serve to strengthen national characteristics.
Keywords: physical training; sports; health; dexterity; activity; development; education